A study of information asymmetry in financial research - Juli Riyanto Tri Wijaya; Eliada Herwiyanti (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to determine the effect of information asymmetry on earnings management, accounting fraud, budgetary slack, and the cost of equity. This study is conducted using literature study techniques by finding facts and making interpretations. Data sources are obtained from the results of previous studies, from 2017 to 2020, which have been published in various national journals. This study concludes that information asymmetry has a positive effect on earnings management; information asymmetry has a positive effect on accounting fraud; information asymmetry has a positive effect on budgetary slack; and information asymmetry has a negative effect on the cost of equity.